การประเมินผลกระทบของแรงดันตกชั่วขณะโดยใช้หลักการระบุตำแหน่ง ความผิดพร่องในระบบจำหน่ายด้วยเส้นโค้ง ITIC: Evaluation of Voltage Sag Impact by Method of Fault Position in Distribution System with ITIC curve - Posree, Rittipad; Sirisumrannukul, Somporn (Asian Health, Science and Technology Reports, 2016)
แรงดันตกชั่วขณะ คือ ปัญหาคุณภาพอย่างหนึ่งสำหรับระบบจำหน่ายไฟฟ้าแบบเหนือดินซึ่งมีโอกาสเกิดความผิดพร่อง หรือการลัดวงจร ผลกระทบของแรงดันตกชั่วขณะเนื่องจากความผิดพร่องหรือการลัดวงจรขึ้นอยู่กับขนาดกระแสและระยะเวลา ในการกำจัดความผิดพร่องของอุปกรณ์ป้องกัน ปัจจัยทั้งสองดังกล่าวทำให้ทราบถึงระดับความลึกและระยะเวลาของการเกิดแรงดัน ตกชั่วขณะ ด้วยการอ้างอิงกับกราฟ ITIC เราจะทราบว่าอุปกรณ์ที่มีความไวที่เชื่อมต่ออยู่ ณ บัสที่สนใจ สามารถทำงานได้อย่างเหมาะสมหรือไม่ บทความนี้นำเสนอวิธีการระบุตำแหน่งของความผิดพร่องเพื่อให้ได้ขนาดและจำนวนครั้งของการเกิดเหตุการณ์แรงดันตก ซึ่งอ้างอิงกับข้อมูลที่ทราบค่าแน่นอนและข้อมูลเชิงสุ่มของระบบ วิธีที่พัฒนาขึ้นได้ทำการทดสอบกับระบบจำหน่าย Roy Billinton Test System (RTBS) ผลการจำลองเหตุการณ์ที่ได้รับเป็นประโยชน์อย่างมากและเป็นแนวทางสำหรับผู้ใช้ไฟฟ้าในการตัดสินใจหาจุดสมดุลระหว่างต้นทุนในการป้องกันเหตุการณ์แรงดันตกชั่วขณะและผลกระทบทางเศรษฐกิจเนื่องจากแรงดันตกชั่วขณะ Voltage sag is one of the main power quality problems in overhead distribution systems which are exposed to faults or short circuits. The effects of voltage sag from fault or short circuit generally depend on fault current magnitude and clearing time of protective device. These two factors determine the depth and duration of voltage sag. With reference to the ITIC curve, it can be determined whether sensitive equipment connected at the bus of interest can function properly This paper presents a method of fault position to obtain the magnitude of voltage and the number of voltage sag events based on deterministic data and statistical data of the system. The developed methodology was tested with the Roy Billinton Test System (RTBS). The simulation results obtained are very useful and can be served as a guideline for customers to justify the optimal balance between the cost of investment to guard against voltage sag events and the economic loss due to voltage sag events.